2013
DOI: 10.1007/s00204-013-1096-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetyl-l-cysteine on target sites of hydroxylated fullerene-induced cytotoxicity in isolated rat hepatocytes

Abstract: The effects of N-acetyl-L-cysteine (NAC) on cytotoxicity caused by a hydroxylated fullerene [C60(OH)24], which is known a nanomaterial and/or a water-soluble fullerene derivative, were studied in freshly isolated rat hepatocytes. The exposure of hepatocytes to C60(OH)24 at a concentration of 0.1 mM caused time (0-3 h)-dependent cell death accompanied by the formation of cell blebs, loss of cellular ATP, and reduced glutathione (GSH) and protein thiol levels, as well as the accumulation of glutathione disulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…It is well known that intracellular GSH works as a free radical scavenger, which protects cells against ROS, and that the accumulation of proteins with irreversible thiol oxidation is a parameter of ROS-induced cellular damage (Kettenhofen & Wood, 2010). It was reported that the mitochondrial sulfhydryl group was also a critical target site for chemical compounds in rat hepatocytes (Calabrese, Morgan, & Riemer, 2017;Chernyak & Bernardi, 1996;Nakagawa et al, 2014). Previous studies showed that the oxidation of GSH to GSSG caused the formation of mixed disulfides between GSSG and cellular protein thiols and that a factor in their formation is related to the concentration of intracellular GSSG (Fawthrop, Boobis, & Davies, 1991;Nakagawa, Moldéus, & Cotgreave, 1992;Reed, 1990), suggesting that a slight loss of protein thiols caused by DETX may be dependent on the formation of mixed disulfides ( Figure 4).…”
Section: Comparative Cytotoxic Effects Of Xanthone and Thioxanthonementioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that intracellular GSH works as a free radical scavenger, which protects cells against ROS, and that the accumulation of proteins with irreversible thiol oxidation is a parameter of ROS-induced cellular damage (Kettenhofen & Wood, 2010). It was reported that the mitochondrial sulfhydryl group was also a critical target site for chemical compounds in rat hepatocytes (Calabrese, Morgan, & Riemer, 2017;Chernyak & Bernardi, 1996;Nakagawa et al, 2014). Previous studies showed that the oxidation of GSH to GSSG caused the formation of mixed disulfides between GSSG and cellular protein thiols and that a factor in their formation is related to the concentration of intracellular GSSG (Fawthrop, Boobis, & Davies, 1991;Nakagawa, Moldéus, & Cotgreave, 1992;Reed, 1990), suggesting that a slight loss of protein thiols caused by DETX may be dependent on the formation of mixed disulfides ( Figure 4).…”
Section: Comparative Cytotoxic Effects Of Xanthone and Thioxanthonementioning
confidence: 99%
“…On the other hand, rat hepatocytes were preincubated with NAC at a concentration of 5.0 mM for 15 minutes before the addition of photoinitiators. The concentrations of NAC and fructose used in this study were referred to the ranges in previous studies (Cannon, Harvison, & Rush, 1991;Nakagawa et al, 2014;Nakagawa, Suzuki, & Inomata, 2018). Corresponding control groups received an equivalent volume of DMSO.…”
Section: Isolation and Cell Culture Incubation Of Hepatocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are the major sources of intracellular energy (i.e., ATP), which is necessary for sustaining the structural integrity and proper function of the cytoskeleton because each actin molecule is bound to an ATP or ADP molecule. Multiple studies have suggested that inorganic NPs can affect intracellular ATP synthesis by disrupting mitochondrial function [62,63]. The conformational changes of the cytoskeleton are dependent on ATP, as well as motor proteins, such as myosin, dynein and kinesin, which move along MFs and MTs by interacting with actin and tubulin; the process utilizes energy obtained from ATP hydrolysis.…”
Section: Intracellular Energetic Balance Dysfunctionsmentioning
confidence: 99%
“…Although fullerenols are more soluble than unmodified C 60 , further enhancement in their solubility is necessary for a precise evaluation of their biological activities and for extensive biomedical applications. In addition, some researchers have reported that fullerenol shows cytotoxic effects that are dependent on the number of hydroxyl groups contained by the molecule [15,16]. Therefore using fullerenol with a minimum number of hydroxyl groups would be a desirable approach for pharmaceutical applications of fullerenol.…”
Section: Introductionmentioning
confidence: 99%